Impact of green trade on green growth in Malaysia: A dynamic ARDL simulation - Razelan, Nor Dahlia; Hamidi, Hakimah Nur Ahmad; Zainuddin, Muhamad Rias K V; Khairuddin, Nurul Aishah; Zulkifli, Muhamad Solehuddin (Center of Biomass & Renewable Energy (CBIORE), 2024)
Green economic growth emphasizes developing an economy that safeguards natural resources, enhances resource capabilities, and promotes sustainable resource utilization. This approach is vital for balancing economic development with environmental preservation, highlighting the efficient and sustainable use of renewable and non-renewable resources to maintain a clean environment and societal well-being. It also stresses the long-term preservation of natural resources for green growth and prosperity. Environmental sustainability is key for economic growth, as poor sustainability can lead to economic decline due to inefficient resource use. The Eleventh Malaysia Plan highlights the importance of green economic growth, focusing on areas such as creating a supportive environment for green growth, adopting sustainable consumption and production practices, conserving natural resources, and strengthening resilience against climate change and natural disasters. This study examines the impact of natural resource use on the green economic growth in Malaysia from 1990 to 2021, with a focus on green trade as a key component. To achieve this objective, this study utlizies the Autoregressive Distributed Lag (ARDL) method and also its extension, the Dynamic ARDL (DYNARDL). Estimation results for both model indicate that green trade has a significant long run positive impact on green economic growth. While for short run, only DYNARDL method found evidence for positive impact of green trade. These findings suggest that policymakers should further promote green trade as a means to enhance sustainable and equitable resource use, thereby supporting the growth of the green economy in Malaysia.